Rumen degradability of some Algerian browse plant species from Algerian arid rangelands - Boufennara S.; Bouazza L.; Bodas R.; Ammar H.; Bousseboua H.; López S. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The study was conducted in Boussâda district, in the arid Saharan Atlas region with the objective of evaluating the chemical composition and in situ rumen degradation of Algerian browse plants collected from arid rangelands. Six browse plant species were used in this study: four dicotyledon plants namely Atriplex halimus, Artemisia herba-alba, Astragalus gombiformis and Calobota saharae and two monocotyledon plants, namely Lygeum spartum and Stipa tenacissima. Nylon bags containing foliage samples of each species were incubated for 0, 24 and 96 h (as indicators of solubility, degradation rate and potential degradability of the forages) in the rumen of three Merino sheep fitted with rumen fistula. Forages showed different (P<0.001) DM and NDF dissapearance rates. After 96 hours of incubation time, the highest in sacco DM disappearance was observed for A. gombiformis (0.85 g/g DM incubated) and the lowest was obtained with S. tenacissima (0.31 g/g DM incubated). In summary, dicot plants with high protein, low fiber and high DM ruminal degradability could be regarded as interesting roughages for use as ruminant feedstuffs.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)